2021
DOI: 10.1542/peds.2020-048389
|View full text |Cite
|
Sign up to set email alerts
|

Infant Deaths From Medical Causes After a Maltreatment Report

Abstract: OBJECTIVES: To examine whether postneonatal infants reported for maltreatment face a heightened risk of deaths attributable to medical causes.METHODS: Birth and death records for all children born in California between 2010 and 2016 (N 5 3 455 985) were linked to administrative child protection system records. Infants were prospectively followed from birth through death or age 1 year. Reports of maltreatment and foster care placement episodes were modeled as time-varying covariates; sociodemographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…This study provides evidence that infants reported for child maltreatment are at an increased risk of death from medical causes 2. Similar work has not been undertaken in the UK, where health and social care structures differ from those in the USA.…”
Section: Commentarysupporting
confidence: 60%
See 1 more Smart Citation
“…This study provides evidence that infants reported for child maltreatment are at an increased risk of death from medical causes 2. Similar work has not been undertaken in the UK, where health and social care structures differ from those in the USA.…”
Section: Commentarysupporting
confidence: 60%
“…The authors of the study conclude that ‘differences in death rates signal potential unmet service needs among infants who remain at home after reports’ 2. The general paediatrician can play an important role in meeting this need and there should be a low threshold for medical follow-up after a child protection medical assessment, particularly in children who have had more than one episode of reported maltreatment.…”
Section: Commentarymentioning
confidence: 99%
“…Fifth, the data suggest that mothers incarcerated in state prison have different birth characteristics than nonincarcerated mothers in California. In comparison to demographics documented using California’s birth records (Putnam-Hornstein & Needell, 2011 ; Schneiderman et al, 2021 ), incarcerated mothers were more likely to be Black (15% vs. 5%), less likely to have a high school degree (50% vs. 73%), less likely to have paternity established on the birth record (65% vs. 93%), and more likely to have public health insurance (an indicator of lower income; 72% vs. 49%%) when compared to all mothers. These findings align with research showing Black women are overrepresented among women in prison (Gifford et al, 2021 ) and suggests next-generation consequences of pervasive racial differences in criminal justice involvement and incarceration (Wakefield & Wildeman, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to federal sources, almost one-half (45.4%) of child fatalities in 2019 involved children under the age of one (U.S. Department of Health & Human Services, 2021). In one state specific study, infants reported for maltreatment were almost two times more likely to die of medical causes in the first year of life, compared to all other infants, controlling for baseline risks (Schneiderman, Prindle, & Putnam-Hornstein, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%